Application of lean thinking tools to municipal services - Eira, Inês Sofia Oliveira da (2015)
Efficiency and effectiveness of services provided by public organisations have impact in customers’ satisfaction. The current research has as main goal to analyse if lean tools create efficiency and effectiveness gains when applied to a specific set of processes from a public service. Accordingly, lean thinking background is considered. The methodology adopted is based on a case study developed in the Education Department of the city council of Arruda dos Vinhos. Direct observation and informal interviews with staff members and customers are performed. Three processes are analysed using Value Stream Mapping (VSM) tools: application for free school meals for students who apply for social benefits, application for “home-school-home” transport allowance, and money refund from transport expenses. The lean tools used are the VSM big picture map, process activity mapping, and spaghetti diagram. Processes’ customers are identified and what they consider value is assessed. Wastes are identified and suggestions for improvement are developed. Findings show that gains in effectiveness are expected if the suggestions provided are implemented, the process would be more accurate and the outcome would be obtained sooner and without mistakes resulting in more value for customers; regarding efficiency, based on the elimination of waste processes’ total times reduction is expected in the three cases (useful time can be reduced by 29% in the first process, 47% in the second, and 34% in the last one), less human resources’ time is required and shorter distances are covered.